2013
DOI: 10.5772/56577
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Marker-Based/Marker-Less Visual Odometry System for Mobile Robots

Abstract: When moving in generic indoor environments, robotic platforms generally rely solely on information provided by onboard sensors to determine their position and orientation. However, the lack of absolute references often leads to the introduction of severe drifts in estimates computed, making autonomous operations really hard to accomplish. This paper proposes a solution to alleviate the impact of the above issues by combining two vision-based pose estimation techniques working on relative and absolute coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As with marker-less methods, closed-loop navigation systems commonly rely on data fusion of inertial sensors and high-delay vision system [15]. GPS and marker-less methods are often combined with marker-based tracking to compensate for inaccuracies and drift [16]. Similar to our use cases, Gonzalez et al [17] describe the AR.Drone autonomous path and navigation planning through a set of rings, with a world model estimated from their relative poses.…”
Section: A Visual Tracking For Uav Navigationmentioning
confidence: 99%
“…As with marker-less methods, closed-loop navigation systems commonly rely on data fusion of inertial sensors and high-delay vision system [15]. GPS and marker-less methods are often combined with marker-based tracking to compensate for inaccuracies and drift [16]. Similar to our use cases, Gonzalez et al [17] describe the AR.Drone autonomous path and navigation planning through a set of rings, with a world model estimated from their relative poses.…”
Section: A Visual Tracking For Uav Navigationmentioning
confidence: 99%
“…Regarding this, we apply a marker-based strategy for the contest. GPS and marker-less methods are often combined with marker-based tracking to compen sate for inaccuracies and drift [16]. Similar to our task, Gonzalez et al [17] describe the AR.Drone autonomous path and navigation planning through a set of rings, with an absolute world model estimated from the relative poses of the rings.…”
Section: Visual Tracking For Uav Navigationmentioning
confidence: 99%
“…Recently it can be observed that the interest in 3D printing technology for manufacturing of flow chip and equipment has been growing [28][29][30][31]. Described technology (lab-on-a-chip) can be extended to the mobile platform (lab-on-a-robot) [26,32,33]. More recently, the first integrated system capable of performing remote analysis of air samples using microchip-CE was presented [33].…”
Section: Introductionmentioning
confidence: 99%
“…The screenprinted electrodes (SPEs) can be used as a suitable detectors in CE microchips [34]. Thus, the technology becomes more accessible in new robotic controls and applications are developed [32,[35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%